2019
DOI: 10.1097/meg.0000000000001215
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance does not impair response of chronic hepatitis C virus to direct-acting antivirals, and improves with the treatment

Abstract: IR does not impair the response of patients with HCV treated with DAAs, and improves significantly in patients who achieve an SVR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
3
7
2
Order By: Relevance
“…Stine et al, when studying a group of 175 patients with chronic hepatitis C treated with DAAs, couldn't show a statistical significance in glucose profile before and after treatment (46) .Those results were also shared by Chaudhury et al, who did not identify sustained benefits to glycaemic levels following HCV clearance irrespective of HIV, diabetes or fibrosis stage (47) . It´s interesting to note that our patients had higher levels of HOMA-IR both before and after SVR when compared to other studies (44,48) , which could also justify our findings.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Stine et al, when studying a group of 175 patients with chronic hepatitis C treated with DAAs, couldn't show a statistical significance in glucose profile before and after treatment (46) .Those results were also shared by Chaudhury et al, who did not identify sustained benefits to glycaemic levels following HCV clearance irrespective of HIV, diabetes or fibrosis stage (47) . It´s interesting to note that our patients had higher levels of HOMA-IR both before and after SVR when compared to other studies (44,48) , which could also justify our findings.…”
Section: Discussionsupporting
confidence: 83%
“…The exact effects of virus C treatment on glucose profile are still not completely known, although some studies show a direct relation between SVR and decreasing IR (39,40,41,42,43) . Elhelbawy et al, when researching 511 patients treated for HCC with the new DAAs, showed a significant reduction on IR (44) . A study by Ciancio et al on 101 patients shares this conclusion, while also demonstrating a decrease in fasting glucose and glycated haemoglobin (45) .…”
Section: Discussionmentioning
confidence: 99%
“…After the widespread adoption of highly effective direct‐acting antivirals (DAAs), preliminary data from case series and cohort studies confirmed what previously described in the IFN era . However, most of them were mono‐centric and/or retrospective, with a relatively short duration of follow‐up.…”
Section: Introductionsupporting
confidence: 54%
“…Compared to interferon and ribavirin therapies alone, DAAs have higher potency, higher safety, lower side effects and shorter treatment durations and have been widely used in most countries. Insulin resistance did not impair the response of CHC patients treated with DAAs 29 . Currently, many studies on DAA treatments for HCV have also demonstrated the potential benefit in glucose metabolism after SVR [30][31][32][33][34][35][36] .…”
Section: Continuedmentioning
confidence: 79%